Adherence to immunoprevention: how to change the situation? - N. I. Briko; A. Ya. Mindlina; N. P. Galina; V. A. Korshunov; R. V. Polibin (Фундаментальная и клиническая медицина)
Aim. Immunoprevention represents a well-established tool to prevent and eliminate life-threatening infectious diseases. However, low adherence in the population is a major obstacle to achieve the full coverage of preventive vaccinations. Here we studied the adherence of various population groups and healthcare workers to vaccination.Materials and Methods. We conducted an original survey among 1147 university students, 214 parents and 512 physicians.Results. Among the students of humanitarian and technical faculties, only 33% and 37% respectively showed a positive attitude to immunoprevention. This indicator, however, was higher in medical students and physicians (76% and 80%, respectively). Overall awareness of all population groups on immunization is insufficient to perform such measures efficiently. The reasons of low adherence include anti-vaccine propaganda, negative attitude and lack of awareness of healthcare workers on immunoprevention efficiency.Conclusion. Further large efforts are urgently needed to increase the adherence to immunization both in general population and healthcare professionals. The primary task is to eliminate the lack of information on the role and importance of immunization in maintaining population health.